Effective Methods of Passing Examples of The Narrative Genre In Reading Lessons Based on Interactive Methods - SAPAYEVA, Layla; Roziyeva, M.Y. (Researchparks Publishing, 2023)
The article describes effective methods of passing examples of the narrative genre in reading lessons based on interactive methods. To achieve this goal, various forms of lessons –